2021
DOI: 10.1002/jbt.22754
|View full text |Cite
|
Sign up to set email alerts
|

Monocarbonyl curcuminoids as antituberculosis agents with their moderate in‐vitro metabolic stability on human liver microsomes

Abstract: Tuberculosis, an airborne infectious disease, results in a high morbidity and mortality rate. The continuous emergence of TB resistance strains including MDR (multidrugresistant tuberculosis), XDR (extensive drug-resistant tuberculosis), and especially TDR (totally drug-resistant tuberculosis) is a major public health threat and has intensified the need to develop new antitubercular agents. A natural product, curcumin, possesses diverse biological activities but suffers due to a lack of water solubility and bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 45 publications
(56 reference statements)
0
1
0
Order By: Relevance
“…The determination of the structural derivatives of curcumin was obtained through the compilation of relevant research literature. Alterations in the quantity of methoxy and hydroxy groups on the phenyl ring substituents of curcumin exhibited varying degrees of influence on its polarity, water solubility, and pharmacological efficacy. Monocarbonyl curcumin, dihydrocurcumin, tetrahydrocurcumin, and octahydrocurcumin had been demonstrated to outperform curcumin in terms of stability, bioavailability, and activity. Based on the aforementioned reasons, we had identified the substitution positions and quantities of methoxy and hydroxy groups on the phenyl ring of curcumin as well as structural modifications of double bonds and β-diketones on the backbone. Ultimately, curcumin derivatives were obtained through a linear arrangement for CADD analysis.…”
Section: Methodsmentioning
confidence: 99%
“…The determination of the structural derivatives of curcumin was obtained through the compilation of relevant research literature. Alterations in the quantity of methoxy and hydroxy groups on the phenyl ring substituents of curcumin exhibited varying degrees of influence on its polarity, water solubility, and pharmacological efficacy. Monocarbonyl curcumin, dihydrocurcumin, tetrahydrocurcumin, and octahydrocurcumin had been demonstrated to outperform curcumin in terms of stability, bioavailability, and activity. Based on the aforementioned reasons, we had identified the substitution positions and quantities of methoxy and hydroxy groups on the phenyl ring of curcumin as well as structural modifications of double bonds and β-diketones on the backbone. Ultimately, curcumin derivatives were obtained through a linear arrangement for CADD analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, the antimycobacterial activity was decreased by adding a methoxy group to the aromatic ring, while replacing the methoxy group with an ethoxy group had no significant effect. [ 156 ]…”
Section: Bioactivity Of Diarylpentanoids: Anti‐infective Propertiesmentioning
confidence: 99%
“…The authors reported that these compounds are nonhemolytic, nontoxic, and stable under physiological and reducing conditions. Apart from that, compound 89 has moderate in vitro metabolism by liver human microsomes (halflife of 1.2 h; intrinsic clearance of 1.12 mL/h/mg) [69].…”
Section: Antibacterial Activitymentioning
confidence: 99%